New approaches towards understanding trypanosome mitosis - Stretton, Owen (2017)
The protozoan parasite, Trypanosoma brucei has an unusual genome, consisting of an unusually large number of chromosomes. It is composed of 11 large diploid chromosomes and over 100 small linear chromosomes, known as intermediate chromosomes and minichromosomes. These smaller chromosomes contain a portion of a library of genes required for antigenic variation and, therefore, evasion of the host’s immune response. Despite their number, all chromosomes are separated with fidelity during mitosis, through interaction with the mitotic spindle. Animal and fungal model organisms have been widely used to study mitosis and the proteins involved. T. brucei, however, belongs to a group of organisms that diverged from the animal-fungus lineage at or close to the eukaryotic root. Mitosis in trypanosomes differs from that observed in model organisms, including an apparent lack of conserved microtubule motor proteins that drive spindle function and a reduced number of kinetochores. It is, therefore, not well understood how trypanosomes segregate their genomes. In this thesis, I will present the development of an RNA interference based library methodology for the investigation of microtubule motor function. This system uses a combinatorial library that accounts for interactions, such as redundancy, which can occur between motors. I demonstrate that motor redundancy can occur in trypanosomes, by knocking down flagellar kinesin-2 motors. The library approach allows for exploration of an individual motor’s contribution to fitness and, by combining the library with a negative selection marker tag of individual chromosomes, the motor’s role in chromosome segregation. The use of a negative selection marker also allows for quantification of chromosome loss, as I demonstrate by quantifying the losses caused by depletion of the mitotic motor KIN13-1 and the kinetochore protein KKIP1. I also present the development of a cell line to be used in validating the results of the library experiments. The production of a tag that uses KIN13-1 to label the mitotic spindle, for later observations of spindle defects, is presented. Finally, I present the development of a chromosome label that uses arrays of Lac operator repeats and fluorescently labelled Lac repressor protein to tag DNA elements, to follow chromosomes through the cell cycle. I demonstrate this label’s use in detecting chromosome loss and non-disjunction events after knockdown of KIN13-1 and KKIP1. I then use it to demonstrate interactions between chromosomes and kinetochores during mitosis. These data provide evidence that refutes a “lateral stacking” model for chromosome segregation.